Body Image Dissatisfaction and Impulse Buying: A Moderated Mediation Model - Cai, Zhihui; Gui, Yang; Wang, Dandan; Yang, Han; Mao, Peipei; Wang, Zhikeng (Frontiers in Psychology, 2021)
This study investigated the mediating roles of self-acceptance and self-esteem in the relationship between body image dissatisfaction and impulse buying, and tested the moderating effect of gender on the relationships. A sample of 374 college students and graduate students (33.4% male, 66.6% female) participated in the study. Results revealed that (a) body image dissatisfaction positively associated with impulse buying; (b) self-esteem plays a mediating role between body image dissatisfaction and impulsive buying; (c) a serial indirect pathway (i.e., Body image dissatisfaction  → self-acceptance   → self-esteem  → impulse buying) emerged; (d) the mediation path from self-acceptance to self-esteem was stronger for female than that from male. The results underscore the importance of identifying the mechanisms that moderate the mediated path between body image dissatisfaction and impulse buying among students. These findings point to the potential implications about how to reduce impulse buying through improving body image satisfaction.